Implementasi Permensos Republik Indonesia Nomor 20 Tahun 2019 Di Kelurahan Kedondong Raye Kecamatan Banyuasin III Kabupaten Banyuasin - Citra Iasha; Fitria Dwi Lestari (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 20 of 2019 concerning Distribution of Non-Cash Social Assistance developed by the Government to improve the economy of poor families. The election for the implementation of the BPNT program in the Kedondong Raye Village is not necessarily determined by the central government, in this case the Indonesian Ministry of Social Affairs will go through a predetermined election mechanism. The criteria for selecting the implementation of the BPNT program were: high rates of poverty and malnutrition. Apart from being based on these data criteria, what is no less important is the regional commitment to implement the BPNT program. The formulation of the problem in this study, how is the implementation of the Non-Cash Food Assistance (BPNT) program in improving the economy of poor families in Kedondong Raye Village, Banyuasin III District, Banyuasin Regency. This type of research is qualitative research using a sociological approach. The data sources used are primary data and secondary data. Data collection techniques used are interviews, observation, and documentation. The validity of the data used is source triangulation, technical triangulation, and time triangulation. Data analysis used is data reduction, data presentation, and conclusions. The results show that the Kedondong Raye Kelurahan BPNT program that is implemented can make the community more independent in conducting non-cash transactions at the BPNT e-Warong Program and help the community in an economic sense. Improving the effectiveness of social assistance in a non-cash way in providing food, and encouraging financial inclusion, namely involving the community to become entrepreneurs.